Методичні аспекти оцінки гендерного впливу реалізації стратегії розвитку територіальної громади - Лісовська, Л. С.; Lisovska, L. (Видавництво Львівської політехніки, 2024)
Дослідження спрямовано на удосконалення методичних основ забезпечення гендерної рівності в управлінні місцевим розвитком. У статті обґрунтовано методичні аспекти оцінювання гендерного впливу від дії планових документів у діяльності органів місцевого самоврядування. Автор сформувала загальну послідовність етапів оцінювання гендерного впливу, охарактеризувала їх змістове наповнення. Розглянуто систему гендерно чутливих індикаторів та обґрунтовано критерії для ранжування проєктів, які покладено в основу оцінювання гендерного впливу. Розроблений методичний підхід використано для оцінювання гендерного впливу дії стратегії розвитку територіальної громади України, наведено результати застосування методичного підходу.

Purpose. The purpose of the article is to substantiate the main aspects that form a methodological approach to assessing the gender impact of the action and implementation of the Territorial Community Development Strategy. Design/methodology/approach. Semantic analysis, comparative analysis and the systematisation method were used to form a system of gender-sensitive indicators; the grouping method and structural and logical modelling were used to develop a rationale for the sequence of gender impact assessment. The abstract and logical method was used to formulate conclusions and theoretically summarise the results of the study. Findings. The main task of conducting a gender impact assessment of a community development strategy is to determine whether certain programmes or development processes have contributed to or hindered the implementation of gender equality principles in the community. Based on the analysis of scientific and methodological sources, the article presents the gender impact assessment as a set of mutually agreed stages. At the first stage, the goals, principles and target groups of gender-sensitive groups are established. A gender analysis is conducted to identify existing gender roles and the challenges and obstacles to equal participation that they pose for gender-sensitive groups. The development of a gender-responsive methodology includes the creation of a system of methods, rules, principles and approaches aimed at assessing gender equality and determining the impact of a particular community development strategy on gender aspects. In order to assess gender impact, the article develops a system of gender-sensitive indicators. Presentation of the results, conclusions and recommendations in the gender impact assessment of the action or implementation of the community development strategy is the final stage. At this stage, a detailedpresentation of the information obtained is made, and the main conclusions are formulated regarding the identified gender inequalities and the specifics of the impact of the programme document on gender-sensitive groups. The results of the assessment and recommendations can be made public to the public and other stakeholders, and public discussions and hearings can be organised, as well as consultations with residents of the local community to ensure broad participation and involvement of different groups. The developed conclusions and recommendations are usually documented in the form of a report. The proposed methodological approach to gender impact assessment was tested on the data and information contained in the Development Strategy of Velyky Bychkivska settlement territorial community for the period up to 2027. The Velyky Bychkiv territorial community is located in the Rakhiv district of the Zakarpattia region of Ukraine. Practical implications. The practical implications encompass the development of a more effective methodological approach for assessing gender impact within the context of territorial community development strategies. This contribution holds significance for local self-government bodies, governmental entities, activist groups, and other stakeholders involved in the process. Implementing the proposed methodological approach has the potential to enhance the overall management of territorial development, ensuring a more efficient consideration of gender aspects in decision-making processes. Moreover, it can contribute to heightened gender sensitivity among participants involved in the decision-making process, fostering a more inclusive and equitable approach to strategic community development. Originality/value. The originality and value of the article lie in its innovative methodological approach to evaluating the gender impact of implementing the Territorial Community Development Strategy. The article introduces a comprehensive framework that not only identifies and analyzes gender-specific factors at various stages but also offers practical recommendations for addressing gender inequalities within the context of community development. This contribution adds unique insights to the existing literature by providing a nuanced and context-specific methodology tailored to the intricacies of territorial community development. The article's value extends to practitioners, policymakers, and researchers engaged in gender-responsive planning, offering a practical tool to enhance the effectiveness and inclusivity of strategic development initiatives.
Methodological aspects of assessing the gender impact implementation of the territorial community development strategy
Keywords: гендер; органи місцевого самоврядування; гендерна рівність; оцінка гендерного впливу; gender; local self-government bodies; gender equality; gender impact assessment; J16; H79; 342.722.1